Manajemen Strategik Pembelajaran di MI Ma’arif NU 1 Tunjungmuli - Fadlun Fadlun (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
This research is motivated by the importance of a quality learning process. This study aims to reveal the strategic management of learning at MI Ma'arif NU 1 Tunjungmuli. The approach used in this research is qualitative. The research subjects were determined by purposive sampling technique, which consisted of madrasa heads, teachers and students. Research data were collected through in-depth interviews, participant observation, and document analysis. The research data were analyzed using interactive analysis techniques developed by Miles & Huberman, namely: data reduction, data presentation, and drawing conclusions. This research shows three guests. First, learning strategic planning at MI Ma'arif NU 1 Tunjungmuli is carried out by formulating every existing program, the head of the madrasa always formulates and holds deliberations with the board of teachers and all existing stakeholders to equate the vision, mission and steps to achieve it. Second, the implementation of the learning strategy at MI Ma'arif NU 1 Tunjungmuli is carried out in stages and in an organized manner, always accompanied by a foundation, surveyed for its activities and intense mentoring, as well as an open leadership model. Third, strategic evaluation of learning at MI Ma'arif NU 1 Tunjungmuli is by: (a) directly observing student behavior in everyday life; (b) evaluations carried out both formally and informally; (c) see directly changes in student behavior after receiving coaching; (d) evaluation carried out in weekly, monthly, semi-annual, year-end and early-year evaluation activities.